2018
DOI: 10.1063/1.5026640
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquids make DNA rigid

Abstract: Persistence length of double-stranded DNA (dsDNA) is known to decrease with an increase in ionic concentration of the solution. In contrast to this, here we show that the persistence length of dsDNA increases dramatically as a function of ionic liquid (IL) concentration. Using all atom explicit solvent molecular dynamics simulations and theoretical models, we present, for the first time, a systematic study to determine the mechanical properties of dsDNA in various hydrated ILs at different concentrations. We f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 60 publications
5
39
0
Order By: Relevance
“…The orientational correlation between distant portions of the helical molecule may be lost due to disordering thermal fluctuations or to interactions with the surrounding solvent. Such effects vary both with the sequence specificities and type of solvent [28] thus concurring to determine the flexibility properties as measured by the l p [29]. For semi-flexible polymers the latter is defined as the characteristic decay length of the correlation between two bond vectors, d i ≡ d i,i−1 and d k ≡ d k,k−1 , that is:…”
Section: Persistence Lengthmentioning
confidence: 97%
“…The orientational correlation between distant portions of the helical molecule may be lost due to disordering thermal fluctuations or to interactions with the surrounding solvent. Such effects vary both with the sequence specificities and type of solvent [28] thus concurring to determine the flexibility properties as measured by the l p [29]. For semi-flexible polymers the latter is defined as the characteristic decay length of the correlation between two bond vectors, d i ≡ d i,i−1 and d k ≡ d k,k−1 , that is:…”
Section: Persistence Lengthmentioning
confidence: 97%
“…The alkyl side chain of an imidazolium cation may participate in aggregation and association with anions in bulk ILs, although the hydrophilic and Coulomb forces remain the dominant interactions [11][12][13][14][15]. On top of that, several reports [17][18][19][20][21][22][23][24] show that the hydrophobic alkyl chains can stabilize biopolymers like nucleic acids via forming the association through electrostatic interactions between the DNA molecule and cations of IL.DNA molecules can associate with cations of IL via the negatively charged backbone and hydrophobic groove interaction of DNA [19][20][21][22][23][24]. The cluster structure of ILs can be disturbed by mixing with an additive-like DNA via electrostatic interaction between the cation head group of ILs and phosphate anion of DNA and hydrophobic association between the alkyl part of IL cation and the groove region or nitrogenous base of DNA [19][20][21][22][23][24].…”
mentioning
confidence: 99%
“…Part of base pairs (pyrimidine and purine), which interact via hydrogen bonding and stacking, are easily attracted to alkyl tail of ILs with noncovalent interaction, hydrophobic interaction, or van der Waals force. Several researchers [19][20][21][22] have suggested that the chemical structure of the cationic head group of ILs determines the electrostatic interaction to a certain extent, whereas the alkyl chain length of the cation is responsible for the stability of groove association. Ghoshdastidar et al [25] have reported that ILs can rescue DNA by forming a complex via specific trapping force in water solutions.…”
mentioning
confidence: 99%
See 2 more Smart Citations